2013
DOI: 10.3171/2013.6.spine121129
|View full text |Cite
|
Sign up to set email alerts
|

Failure of lumbopelvic fixation after long construct fusions in patients with adult spinal deformity: clinical and radiographic risk factors

Abstract: Object Lumbopelvic fixation provides biomechanical support to the base of the long constructs used for adult spinal deformity. However, the failure rate of the lumbopelvic fixation and its risk factors are not well known. The authors' objective was to report the failure rate and risk factors for lumbopelvic fixation in long instrumented spinal fusion constructs performed for adult spinal deformity. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 14 publications
2
69
2
1
Order By: Relevance
“…3,10,18,23 Additionally, complications are not uncommon. Cho et al reported that the complication rate for degenerative lumbar scoliosis was 68%.…”
Section: Discussionmentioning
confidence: 99%
“…3,10,18,23 Additionally, complications are not uncommon. Cho et al reported that the complication rate for degenerative lumbar scoliosis was 68%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review, however, included failure at the level above the lumbosacral junction (L4-5) as a major complication of pelvic fixation. 8 This phenomenon may occur because of construct failure originating at either the rostral or caudal end. Possible mechanisms of both types of failure are described below.…”
Section: Pseudarthrosismentioning
confidence: 99%
“…34 Three of the 37 patients (8%) in our study who received iliac bolts underwent removal of the pelvic fixation because of painful hardware prominence, which is consistent with the rates of iliac bolt removal reported in other studies (3%-34%). 8,15,17,24,34 The rate of patients experiencing pain relief after implant removal varies widely (12%-70%). 2,3,10,13,31 Removal of instrumentation is not a benign procedure, and previous studies have reported progression of deformity after removal.…”
Section: Painful Hardware Prominencementioning
confidence: 99%
“…Screw loosening, represented as a radiolucent area around the screw, indicates loss of screw fixation and potential progression to pseudarthrosis 1,17) . The prevalence of iliac screw loosening after long spinal fusion is known to be particularly high (7.5-52%) 3,11,22) . In this study, the iliac screw loosening incidence rate (15/193 screws, 7.8%) was similar to that of a previous report.…”
Section: Discussionmentioning
confidence: 99%